2016
DOI: 10.1111/1467-954x.12426
|View full text |Cite
|
Sign up to set email alerts
|

Gendering the middle classes: the construction of conductors’ authority in youth classical music groups

Abstract: While many accounts of gendered embodiment focus on transformation, this article examines how normative gendered identifications are reinforced among middle-class young people playing classical music. Drawing on an ethnographic study of young people in youth orchestras and a youth choir in the south of England, it examines how the authority of the male conductor is constructed and experienced. It explores the construction of the charisma on which this gendered authority is based, through embodied craft, sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…These findings seem to suggest that class differences in classical music are in part about provision, but it appears that there is also a link between classical music education and middle-class culture. Bull’s (2015, 2016a, 2016b) study of young people playing in youth classical music groups argues that this link is evident in the long-term investment over time required for classical music; the embodied norms of restraint and control; and the formal modes of social organisation such as deference to authority. This link is significant because most classical musicians have to commence training at a very early age in order to compete professionally, as Wagner’s (2012, 2015) transnational research has shown.…”
Section: Producing Classical Musicmentioning
confidence: 99%
“…These findings seem to suggest that class differences in classical music are in part about provision, but it appears that there is also a link between classical music education and middle-class culture. Bull’s (2015, 2016a, 2016b) study of young people playing in youth classical music groups argues that this link is evident in the long-term investment over time required for classical music; the embodied norms of restraint and control; and the formal modes of social organisation such as deference to authority. This link is significant because most classical musicians have to commence training at a very early age in order to compete professionally, as Wagner’s (2012, 2015) transnational research has shown.…”
Section: Producing Classical Musicmentioning
confidence: 99%
“…Theoretical discussions were continuously expanded with connections to live experiences, to bridge the perception of reality with prospects of wider transformation. (For a very different approach to studying the context of gender perception in musical education, see Bull, 2016).…”
Section: Eclectic Research: Between Ethnography and Social Impactmentioning
confidence: 99%
“…Others, usually younger and in stages of a career that made them more independent from elderly professors, would align with the modern approach to the conductor's role. A review of the sociological literature concerning conductors reveals that sociologists are most interested in the status of women in this profession and how gender and class-related issues influence their work (Bull 2016), as well as their place in the highly hierarchical and male-dominated genre of art (Ravet 2016). Dmitry Khodyakov (2014)…”
Section: Schütz and Becker-two Theorists Of Musicmentioning
confidence: 99%